2003
DOI: 10.1111/j.1572-0241.2003.07222.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the HFE gene in patients with hepatocellular carcinoma

Abstract: OBJECTIVE: Hepatocellular carcinoma (HCC) is a late consequence of severe liver disease. Patients with genetic hemochromatosis may be at risk for HCC, but limited information is available on the relationship of HCC and heterozygosity for the HFE gene mutations. METHODS:HFE mutations (C282Y and H63D) were assessed in 162 consecutive patients (131 men/31 women) with HCC. A total of 159 patients had cirrhosis. The most common etiologies of cirrhosis were chronic viral hepatitis (hepatitis C 39%, hepatitis B 9%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
(35 reference statements)
0
38
0
6
Order By: Relevance
“…The association between rs1800562 and HCC has been controversial. We collected nine eligible association studies (Beckman et al 2000;Lauret et al 2002;Boige et al 2003;Cauza et al 2003;Hellerbrand et al 2003;Willis et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b;Nahon et al 2008) (including 1102 HCC cases and 3766 controls) to do the metaanalysis. By using the genetic analysis method (Thakkinstian et al 2005), we found the recessive model was most applicable to this disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between rs1800562 and HCC has been controversial. We collected nine eligible association studies (Beckman et al 2000;Lauret et al 2002;Boige et al 2003;Cauza et al 2003;Hellerbrand et al 2003;Willis et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b;Nahon et al 2008) (including 1102 HCC cases and 3766 controls) to do the metaanalysis. By using the genetic analysis method (Thakkinstian et al 2005), we found the recessive model was most applicable to this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Homozygosity for mutation (Cys282Tyr, G [ A, rs1800562) in the HFE gene is responsible for the majority of cases of typical phenotypic HH (Ellervik et al 2007). However, the relationship of this mutation and HCC was controversial among reported studies (Beckman et al 2000;Lauret et al 2002;Boige et al 2003;Cauza et al 2003;Hellerbrand et al 2003;Willis et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b;Nahon et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Increased HIC may lead to generation of hydroxyl radicals [41], induce lipid peroxidation [42], and accelerate hepatic fibrosis [8]. Furthermore it may increase the risk for development of hepatocellular carcinoma [5,43]. Finally, iron could interfere with the antiviral and immunomodulatory effects of IFN.…”
Section: Discussionmentioning
confidence: 97%
“…Several teams have reported that the prevalence of HFE C282Y mutations was increased in patients with HCC [71,72]. However, other studies have failed to confirm these associations [73][74][75]. A recent prospective study enabled a link to be made between hepatic iron overload, HFE variations and development of HCC in alcoholic cirrhosis [39] while neither of these two factors affected the risk of liver cancer in HCV-infected cirrhotic patients.…”
Section: Iron Metabolismmentioning
confidence: 89%